Sito: an American teenager and the city that failed him - Ralph, Laurence (Grand Central Publishing, 2024)
"In September of 2019, Luis Alberto Quiñonez-known as Sito- was shot to death as he sat in his car in the Mission District of San Francisco. He was nineteen. His killer, Julius Williams, was seventeen. It was the second time the teens had encountered one another. The first, five years before, also ended in tragedy, when Julius watched as his brother was stabbed to death by an acquaintance of Sito's. The two murders merited a few local news stories, and then the rest of the world moved on. But for the families of the slain teenagers, it was impossible to move on. And for Laurence Ralph, the stepfather of Sito's half-brother who had dedicated much of his academic career to studying gang-affiliated youth, Sito's murder forced him to revisit a subject of scholarly inquiry in a profoundly different, deeply personal way. Written from Ralph's perspective as both a person enmeshed in Sito's family and as an Ivy League professor and expert on the entanglement of class and violence, SITO is an intimate story with an message about the lived experience of urban danger, and about anger, fear, grief, vengeance, and ultimately grace"--